REINTERPRETATION OF HIJAB CONCEPT IN THE VIEW OF MURTADHA MUTAHHARI - Nurul Khair (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2019)
In the view of Millennial society, Hijab was better known as fashion for woman to look beautiful. It’s proven by the presence of so many tutorials wearing Hijab with various models showed on Youtube. Those tutorials influenced women views that to make them look completely enchanting they should wear Hijab. As the consequence, Hijab what must be believed to be an obligation and the guidance of the Shari’a, it’s even understood by women as a form of need and desire only, and it’s especially just to attract man attentions. Former times, Hijab was understood by people as a symbol of glory and a form of the obedience of a woman to God. But, now, due to misunderstanding of the meaning and the essence of Hijab, it’s misused by women in this Millennial era. To solve this problem, it’s required a philosophical study. This study is expected to be one way to refine meaning of the essence of Hijab. To look further, we can study some views of Sayid Murtadha Muthahhari. He was one of contemporary Iranian philosophers who refined the essence of Hijab. In Murtadha Mutahhari philosophical views, he offered to us four meaning of the essence of Hijab, those were the first was psychological tranquility, the second was strengthen the relationship of husband and wife, the third was the glory and honor of women, and the fourth was strengthen of the society. In another hand, he also offered to us three reasons that why women must wear Hijab. It’s economic reasons, social reason, and ethical reason. This Study is trying to refine and inform the meaning of the essence of hijab to Moslem society through Murtadha Mutahhari philosophical view.